The mediating role of self-compassion in the relationship between childhood trauma and the symptoms of body dysmorphic disorder - Motahhareh Kargar Shooroki; Azadeh Choobforoushzadeh; Azra Mohammadpanah Ardakan (BMC Psychology)
Abstract Background Body dysmorphic disorder (BDD) is a prevalent concern among adolescent girls. Childhood experiences of security or insecurity are recognized as significant foundational factors influencing body image and, consequently, the development of BDD. Adolescents with a history of childhood trauma may face an elevated risk of developing psychiatric conditions, including obsessive-compulsive disorder and BDD. This study, therefore, aimed to predict BDD symptoms based on childhood trauma, with self-compassion acting as a mediating factor. This framework integrates principles from cognitive-behavioral theory and attachment theory. Specifically, cognitive distortions stemming from cognitive-behavioral patterns, coupled with diminished self-esteem and self-worth as conceptualized by attachment theory, are believed to contribute to lower self-compassion, subsequently leading to a higher incidence of BDD symptoms. Methods A cross-sectional design employing structural equation modeling (SEM) was utilized to construct an optimal model for BDD symptoms, where the mediating role of self-compassion was tested in the relationship between childhood trauma and BDD symptoms. The study population comprised female students aged 16 to 22 in the cities of Meybod and Ardakan during the 2023–2024 academic year. A non-random convenience sample of 300 participants was selected. Data were collected using the Childhood Trauma Questionnaire (CTQ), the Yale-Brown Obsessive Compulsive Scale-Modified for BDD (BDD-YBOCS), and the Self-Compassion Scale (SCS). Statistical analyses, including Pearson’s correlation coefficient and stepwise multiple regression, were performed using SPSS-26 software. SEM analyses were conducted using AMOS-24 software. Results The study’s results indicated several significant relationships among the variables. Childhood trauma was found to have a significant negative direct effect on self-compassion (β=−0.704, p < 0.001), suggesting that higher levels of trauma are associated with lower self-compassion and vice versa. Conversely, childhood trauma exhibited a significant positive direct effect on BDD symptoms (β = 0.321, p < 0.001), indicating that increased trauma predicts more severe BDD symptoms. Furthermore, self-compassion demonstrated a considerable negative direct impact on BDD symptoms (β=−0.765, p < 0.001), implying that low self-compassion is linked to increased BDD symptomatology and vice versa. Crucially, the Sobel test statistic of 3.216 (exceeding the critical value of 1.96) confirmed that self-compassion significantly mediated the relationship between childhood trauma and BDD symptoms (β = 0.538, p < 0.001). This mediation model suggests that self-compassion plays a vital role in explaining how childhood trauma contributes to the development of BDD symptoms. Conclusion The finding demonstrates a robust model fit, confirming self-compassion’s mediating role in the association between childhood trauma and BDD symptoms. Consequently, interventions aimed at enhancing self-compassion, such as group education programs and therapeutic approaches grounded in self-compassion therapy delivered in established treatment centers, could effectively mitigate the impact of childhood trauma. Such interventions are anticipated to lead to a reduction in BDD symptomatology, particularly by decreasing cognitive distortions related to body image and fostering greater self-acceptance.